Mind wandering and motor control: off-task thinking disrupts the online adjustment of behavior - Kam, Julia W.; Dao, Elizabeth; Blinn, Patricia; Krigolson, Olav E.; Boyd, Lara A.; Handy, Todd C. (Frontiers in Human Neuroscience, 2012)
Mind wandering episodes have been construed as periods of "stimulus-independent" thought, where our minds are decoupled from the external sensory environment. In two experiments, we used behavioral and event-related potential (ERP) measures to determine whether mind wandering episodes can also be considered as periods of "response-independent" thought, with our minds disengaged from adjusting our behavioral outputs. In the first experiment, participants performed a motor tracking task and were occasionally prompted to report whether their attention was "on-task" or "mind wandering." We found greater tracking error in periods prior to mind wandering vs. on-task reports. To ascertain whether this finding was due to attenuation in visual perception per se vs. a disruptive effect of mind wandering on performance monitoring, we conducted a second experiment in which participants completed a time-estimation task. They were given feedback on the accuracy of their estimations while we recorded their EEG, and were also occasionally asked to report their attention state. We found that the sensitivity of behavior and the P3 ERP component to feedback signals were significantly reduced just prior to mind wandering vs. on-task attentional reports. Moreover, these effects co-occurred with decreases in the error-related negativity elicited by feedback signals (fERN), a direct measure of behavioral feedback assessment in cortex. Our findings suggest that the functional consequences of mind wandering are not limited to just the processing of incoming stimulation per se, but extend as well to the control and adjustment of behavior.